PENGARUH HARGA DAN PROMOSI TERHADAP VOLUME PENJUALAN PADA PRODUK KEMASAN TOTAL 8+ PT TIRTAMAS LESTARI DI KOTA TANGERANG - Abdul Haris Hidayat; Novia Susanti (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the effect of price and promotion on sales volume of PT. TOTAL 8+ packaging products. Tirtamas Lestari in Tangerang City. The method used is quantitative. The sampling technique uses probability sampling, which is a sampling technique that provides equal opportunities for each member of the population to be selected as a member of the sample and a total of 100 respondents are obtained. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. Calculations use the SPSS version 27 program. The results of this study are that price has a significant effect on sales volume of PT. TOTAL 8+ packaging products. Tirtamas Lestari in Tangerang City with the results of the hypothesis test obtained tcount > ttable or (4,532 > 1,984). Promotion has a significant effect on sales volume of TOTAL 8+ PT packaging products. Tirtamas Lestari in Tangerang City and with the results of the hypothesis test obtained tcount > ttable or (6,6401 > 1,984). Price and promotion simultaneously have a significant effect on sales volume of TOTAL 8+ PT Tirtamas Lestari in Tangerang City with the regression equation Y = 4,838 + 0.364 X1 + 0.525 X2. The correlation coefficient value obtained is 0.852, meaning that the dependent and independent variables simultaneously have a strong level of strength. The coefficient of determination is 0,726 or 72,6% while the remaining 0.274 or 27,4% is influenced by other factors. The hypothesis test obtained fcount > ftable or (128,775 > 3,090), meaning that there is a significant simultaneous effect between price and promotion on sales volume on packaging products TOTAL 8+ PT Tirtamas Lestari in Tangerang City.